How to attract young people to science? (based on materials of sociological research); IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Karpov D. A. Dmitriy Andreevich (Social and humanitarian aspects of engineering, 2015)
Title screen